VD_FINDINFO Décision / 2011 / 287 vom 26. Mai 2011 - VD Tribunal cantonal (2011)
TÉMOIN ANONYME, AUDITION OU INTERROGATOIRE, TÉMOIN, PROCÈS ÉQUITABLE | 147 CPP (CH), 149 CPP (CH), 393 al. 1 let. a CPP (CH)